General biology (Hunt Valley, MD : Digital Imaging Associates, 1992)
Contains more than 600 images on general biology, botany and genetics that can be incorporated into any Macintosh program or multimedia presentation package.
"Volume III."
Production level cataloging.
Keywords: Biology; Genetics